1977
DOI: 10.1111/j.1744-313x.1977.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatibility Antigens and Other Genetic Markers in Ankylosing Spondylitis and Inflammatory Bowel Diseases

Abstract: SUMMARY Of 118 Dutch patients suffering from ankylosing spondylitis (AS) 81.4% were found to be positive for the HLA antigen B27. The B27 frequency proved to be significantly higher in patients in whom the disease had an early onset. In addition to B27, another HLA antigen may be associated with AS; the antigen Bw16 was found to be significantly increased in B27 negative AS patients. HLA phenotype frequencies were also determined in 109 patients with idiopathic inflammatory bowel disease (IBD). In fifty‐eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…52 6% of the CD-AS patients were HLA B27 positive, which differed significantly from the frequency of HLA B27 in a group of CD patients without AS (3*9 %) studied separately (van den Berg- Loonen et al, 1977) CD-AS and 3 UC-AS patients had at some time in their illness a peripheral arthritis, and in 9 and 2, respectively, joint inflammation ran in parallel with inflammatory bowel activity. The large majority of both CD-AS and UC-AS patients showed a severe form of radiographic sacroiliitis (grade 3 or 4).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…52 6% of the CD-AS patients were HLA B27 positive, which differed significantly from the frequency of HLA B27 in a group of CD patients without AS (3*9 %) studied separately (van den Berg- Loonen et al, 1977) CD-AS and 3 UC-AS patients had at some time in their illness a peripheral arthritis, and in 9 and 2, respectively, joint inflammation ran in parallel with inflammatory bowel activity. The large majority of both CD-AS and UC-AS patients showed a severe form of radiographic sacroiliitis (grade 3 or 4).…”
Section: Resultsmentioning
confidence: 70%
“…The frequency of HLA B27 in UC-AS patients was 66 -7 %. In comparison, UC patients without AS had a frequency of 19% (van den Berg-Loonen et al, 1977), but this was not significant. The frequency of HLA B27 in CD-AS and UC-AS patients differed significantly from the frequency of HLA B27 in a nonselected group of patients with idiopathic AS with no evidence of IBD (81.7%) (van den Berg-Loonen et al, 1977) (P<0-01 and P<0.01 respectively).…”
Section: Resultsmentioning
confidence: 74%
“…However, the difference did not reach statistical significance and the association with HLA-B17 has not been confirmed in other countries, including The Netherlands. Here, a group in Amsterdam (van den Berg-Loonen et al 1977) and our group in Leiden have found, independently of each other, an association with HLA-B18, but again the association is not impressive: 21.6% in patients and 6.9% in controls in Amsterdam and 12.1% in patients as against 6.5% in controls in Leiden.…”
Section: Discussionmentioning
confidence: 49%
“…To date, the search for HLA markers in UC has been inconclusive (Kirsner & Shorter 1982). Several surveys did not find divergences from controls (Corazza et al 1978, Smolen et al 1982, whereas other authors found significant associations with different antigens in different populations (van den Berg-Loonen et al 1977, Delpre et al 1980, Schrumpf et al 1982. Recently, in a Japanese population, an association with B5, DR2 haplotype has been shown (Asakura et al 1982).…”
mentioning
confidence: 94%